2015
DOI: 10.4081/jlimnol.2015.1055
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of phytoplankton communities in a Great Lakes drowned river-mouth lake (Mona Lake, USA)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
1
5
1
1
Order By: Relevance
“…The riverine diatom community showed a dramatic temporal dynamic in this study, in accordance with previous studies468353637. Although the relationship between riverine algae community variations and environmental factors (e.g., resources, disturbances, grazers, etc.)…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The riverine diatom community showed a dramatic temporal dynamic in this study, in accordance with previous studies468353637. Although the relationship between riverine algae community variations and environmental factors (e.g., resources, disturbances, grazers, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…As diatoms strongly respond to environmental changes23456, they are increasingly being employed as bio-indicators to assess ecological conditions in lentic and lotic ecosystems around the world789. Diatoms are a key component of riverine algae and are often the most important primary producers of stream ecosystems46101112.…”
mentioning
confidence: 99%
“…Unlike the spatial variations, phytoplankton functional groups biomass in Dali Nur Lake exhibited a strong seasonal variation. Similar to other lake in temperate regions (Yang et al 2011;Gillett et al 2015), phytoplankton functional groups biomass was dominated by bacillariophyta (groups MP, P, and C) and chlorophyta (X2) in spring corresponding to low temperatures (4 C) and relatively high nutrients. Similarly, Pearson correlation analysis results confirmed that groups MP, P, and C were negatively correlated with WT (Table 3).…”
Section: Spatial and Seasonal Variation Of Phytoplankton Functional Gmentioning
confidence: 57%
“…Guided by the work of Grime (1979) who used the concept of adaptive 'strategies' to identify and characterized life-history and physiological activity of plants, Reynolds (1997) described several phytoplankton functional groups that may possible dominate or co-dominate in a given environment (Reynolds 2006;Reynolds et al 2002). In the recent past, the concept of using phytoplankton functional groups based on the morphological, physiological and ecological characteristics of the specie has proved to be reliable approach to analyze spatial and temporal variations in phytoplankton biomass (Becker et al 2010;Yang et al 2011;Gillett et al 2015;Li et al 2017).…”
Section: Spatial and Seasonal Variation Of Phytoplankton Functional Gmentioning
confidence: 99%
“…It is important to understand what environmental parameters may regulate MC production but to determine what factors influence the variants of MC congeners produced by cyanobacterial blooms. Drowned-river mouth lakes are transitional zones between a lake and an inflowing river and have unique physical and hydrological dynamics19. West Michigan (USA) contains many drowned-river mouth lakes with histories of cyanobacteria blooms2021.…”
mentioning
confidence: 99%